Gambaran Kesulitan Intubasi Berdasarkan Pengulangan Intubasi di Rumah Sakit Umum Daerah Provinsi Papua Barat - Mawuntu, Jordan Herling Turang; Wibowo, Tophan Heri; Handayani, Rahmaya Nova (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
Difficult intubation is a condition in which direct laryngoscopic intubation, with placement of the intubation tube below the laryngeal inlet, is problematic or impossible. Risk factors for difficult intubation include a short and thick neck, a large tongue, impaired neck and jaw mobility, or obesity. The main scope of interest in this article is obesity. In obese patients (body mass index [BMI]>35), difficult intubation is caused by fat accumulation in the oral cavity, cheeks, and a relatively thick tongue. This type of research is a non-experimental qualitative study. The design of this study is descriptive. With a Cross Sectional approach. The sampling technique in this study is total sampling. Total sampling is a sampling technique where the number of samples is the same as the population. Based on the research results obtained from the results of patient anamnesis, it was found that most respondents did not have difficulty intubation or as many as 46 respondents did not experience difficulty intubation or 92.0%, and for respondents who experienced difficulty intubation as many as 4 respondents or 8.0 %.